Effect of text messaging plus peer navigation on viral suppression among youth with HIV in the iCARE Nigeria pilot study (2021)
Background—Consistent with the global trend, youth with HIV (YWH) in Nigeria have high rates of viral non-suppression. Novel interventions are needed. Methods—In a single-arm trial, participants aged 15–24 years old received 48 weeks of a combination intervention, comprising daily two-way text message medication reminders plus peer navigation. The primary outcome measure was viral suppression below 200 copies/mL. Secondary outcomes measures included self-reported adherence on a visual analogue scale and medication possession ratio (MPR), each dichotomized as ≥90% (good) or < 90% (poor) adherence. Outcomes were analyzed using McNemar’s test. Retention in care, intervention feasibility and acceptability, and participants’ satisfaction were also assessed. Results—Forty YWH (50% male) were enrolled: mean age 19.9 years (SD=2.5), 55% perinatally-infected, and 35% virologically suppressed at baseline. Compared to baseline, the odds of virologic suppression was higher at 24 weeks (OR = 14.00, p < 0.001) and 48 weeks (OR = 6.00, p = 0.013). Self-reported adherence (≥90%) increased from baseline at 24 weeks (63%, p = 0.008) and 48 weeks (68%, p = 0.031). MPR ≥90% increased at weeks 24 and 48 (85% and 80%, respectively), achieving statistical significance at 24 weeks only (p = 0.022). Retention in care at 48 weeks was 87.5%. All (37/37) participants at week 48 were fully or mostly satisfied with the intervention. Conclusion—Daily, two-way text message reminders plus peer navigation is a promising combination intervention to improve viral suppression among YWH in Nigeria.